Nasogastric versus nasojejunal tube feeding for severe acute pancreatitis: A systematic review of randomized controlled trials - Carlin-Ronquillo, Andrea (2023)
Early enteral nutrition through a feeding tube is essential for the management of severe acute pancreatitis (SAP). Nasojejunal tube nutrition has been preferred on the assumption that it provided pancreatic rest in comparison to the nasogastric tube. However, nasojejunal tube placement is complex, may delay feeding initiation and can increase hospital costs. Our aim was to compare the efficacy and safety of enteral feeding with a nasogastric tube versus nasojejunal tube in patients with SAP. We searched four databases (PubMed, Web of Science, Scopus, and Embase) until December 1, 2022. We included randomized controlled trials (RCTs) comparing enteral feeding by nasogastric and nasojejunal tubes in patients with SAP. Primary outcome was all-cause mortality. Secondary outcomes were organ failure, infection, complications, surgical intervention, duration of tube feeding and length of hospital stay. Risk of bias assessment was completed independently by two investigators using the Cochrane RoB 2.0 tool. We performed random effects model meta-analyses using the inverse variance method. Effect measures were reported as relative risks (RR) and their 95% CIs for dichotomous outcomes and mean differences (MD) and their 95% CIs for continuous outcomes. We included four RCTs involving 192 patients with SAP. The mean ages ranged between 36 and 62 years old. There was no significant difference in all-cause mortality between the nasogastric and nasojejunal feeding arms (18/98 vs. 23/93; RR 1.34, 95%CI 0.77–2.30; p=0.30). There were no significant differences in all secondary outcomes between feeding arms. There were three RCTs with some concerns of bias, in the randomization process. In conclusion, in patients with SAP, enteral feeding delivered by nasogastric tube was as efficacious and safe as nasojejunal tube. Further randomized controlled trials with more participants and better design are needed to confirm these findings.